A road towards ecological development in China: The nexus between green investment, natural resources, green technology innovation, and economic growth. (August 2022) - Zhang, Hongwei; Shao, Yanmin; Han, Xiping; Chang, Hsu-Ling
Abstract: From the economic perspective, China has made remarkable progress, yet, environmental concerns represent an alarm to the country's long-term prosperity. The associated relationship between green investment, natural resources, green technology innovation, and economic growth has important implications for the environment. Therefore, the present study attempts to investigate the effect of green investment, natural resources, green technology innovation, and economic growth on the ecological footprint in China. For this purpose, the present study utilized the NARDL approach using data from 2000 to 2018. The findings demonstrate that green investment, natural resources, green technology investment, and economic development have a significant positive short- and long-run relationship with the ecological footprint. As a result, it is directed to China government to raise green investment, a strict regulatory environment for the control of natural resources rent, as well as green technology innovation that enables optimum efficiency with little environmental impact, specifically on ecological footprint. Highlights: The study explored green investment and natural resources on the ecological footprint in China. The study used the nonlinear technique for analysis. The result shows green investment and natural resources on the ecological footprint.